Democracy and Reforms - Amin, Mohammad; Djankov, Simeon (2012)
The authors use a sample of 147 countries to investigate the link between democracy and reforms. Democracy may be conducive to reforms, because politicians have the incentive to embrace growth-enhancing reforms to win elections. By contrast, authoritarian regimes do not have to worry as much about public opinion and may undertake reforms that are painful in the short run but bring future prosperity. This paper tests these hypotheses, using data on micro-economic reforms from the World Bank's Doing Business database. These data do not suffer the endogeneity issues associated with other datasets on changes in economic institutions. The results provide robust support for the claim that democracy is good for growth-enhancing reforms.